2009
DOI: 10.1007/s11192-008-2062-3
|View full text |Cite
|
Sign up to set email alerts
|

Publications: German economic research institutes on track

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…DIW Berlin now dominates the field followed by ZEW, which ranks first from 2000 until 2003. Ketzler and Zimmermann (2009) found that the trends shown appear to be fairly robust when applying different weighting schemes for the publication output, in particular when the data are controlled for impact factors and co-authorship. Some differences in the development can be seen when the publication output is measured in relation to the number of researchers at the institutes, which is an indicator for the productivity 9…”
Section: Data and General Surveymentioning
confidence: 99%
See 4 more Smart Citations
“…DIW Berlin now dominates the field followed by ZEW, which ranks first from 2000 until 2003. Ketzler and Zimmermann (2009) found that the trends shown appear to be fairly robust when applying different weighting schemes for the publication output, in particular when the data are controlled for impact factors and co-authorship. Some differences in the development can be seen when the publication output is measured in relation to the number of researchers at the institutes, which is an indicator for the productivity 9…”
Section: Data and General Surveymentioning
confidence: 99%
“…In a related paper, Ketzler and Zimmermann (2009) have previously examined the publication activities of Germany’s economic research institutes in the SSCI index from 2000 until 2006. We update their analysis for 2007–2009.…”
Section: Data and General Surveymentioning
confidence: 99%
See 3 more Smart Citations